2016
DOI: 10.18632/oncotarget.11625
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic roles of the SETDB2 histone methyltransferase in gastric cancer

Abstract: SETDB2 is a histone H3 lysine 9 (H3K9) tri-methyltransferase that is involved in transcriptional gene silencing. Since it is still unknown whether SETDB2 is linked to carcinogenesis, we studied alterations and functions of SETDB2 in human gastric cancers (GCs). SETDB2 protein was highly expressed in 30 of 72 (41.7%) primary GC tissues compared with their normal counterparts by immunohistochemistry. SETDB2 overexpression was significantly associated with the late stage of GCs (P<0.05) and poor prognosis of GC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Studies in patients with CLL with deletion of SETDB2 have shown an associated with disease progression [37]. A recently reported study showed that overexpression of SETDB2 may contribute to disease progression in gastric cancer [38]. These previous studies support the findings of the present study (Supplementary Table 5), and raise the possibility that CNAs function in tumorigenesis by several methods, regardless of their effects on gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in patients with CLL with deletion of SETDB2 have shown an associated with disease progression [37]. A recently reported study showed that overexpression of SETDB2 may contribute to disease progression in gastric cancer [38]. These previous studies support the findings of the present study (Supplementary Table 5), and raise the possibility that CNAs function in tumorigenesis by several methods, regardless of their effects on gene expression.…”
Section: Discussionsupporting
confidence: 90%
“…A potential role in cancer pathogenesis has been suggested by genomic sequencing studies (from The Cancer Genome Atlas; TCGA) revealing various mutations and copy number alterations of SETDB2 in a broad subset of cancers ( Figure S4D ). However, with the exception of a recent report characterizing the role of SETDB2 in a gastric cancer cell line ( Nishikawaji et al, 2016 ), there has been no functional link with oncogenesis. Our studies provide this by demonstrating that SETDB2 overexpression sustains leukemogenesis based on multiple lines of evidence, including mechanistic studies and clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these non-E2A-PBX1 cases do not display upregulation of CDKN2C following SETDB2 knockdown, suggesting oncogenic mechanisms based on alternative downstream target genes (data not shown). Indeed, the lack of overlap between SETDB2 targets identified in E2A-PBX1 + cells and those reported in mouse bone-marrow-derived macrophages ( Schliehe et al, 2015 ), or a gastric cancer cell line ( Nishikawaji et al, 2016 ), suggests that SETDB2 downstream targets are highly dependent on biological context, but the specific mechanisms for SETDB2 recruitment to the respective chromatin sites have not been determined. Furthermore, although SETDB2 has been shown to methylate substrate H3K9me2 peptide in vitro ( Falandry et al, 2010 ), a recent report showed that SETDB2 can positively regulate specific targets independent of its H3K9me3 methyltransferase activity ( Roqueta-Rivera et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…SETDB2 plays important roles in immune system [15][16][17] and embryonic development [18,19]. In cancer research, SETDB2 has been found to be involved in cell cycle dysregulation in acute leukemia [20], associated with the prognosis and metastasis of renal tumors [21], and plays an oncogenic role in gastric cancer [22]. However, the roles and mechanism of SETDB2 in cancer stem cells and breast cancer are not clear.…”
Section: Ivyspringmentioning
confidence: 99%